Career anchors reimagined finding direction and opportunity in the changing world of work - Schein, Edgar H.; Van Maanen, John; Schein, Peter A. (Wiley, 2023)
"Career Anchors helps you explore and better understand your workplace skills and competencies, career motives, and values. Rather than a participant workbook, the fifth edition will be a trade book with a free assessment that's accessible with a unique pin included in the book. With this program, you will gain new insight into your career values and how they relate to your past and future choices. This easy-to-use workbook includes information about career development and updated descriptions of the eight career anchors categories: The rapidly changing world of business including more information on globalization, heightened competition, new technologies, greater organizational instability and uncertainty, and shifting societal values, all of which influence career trajectories and career anchors. Updated descriptions of the career anchors. A role mapping process that helps to consider the various external demands and pressures with suggested action steps. A work career and family/life priority grid that includes suggestions for how the work, family, and personal patterns identified can interact (for better or worse) with each of the eight career anchors. An updated "looking ahead" section that begins with a comprehensive look at how the world of work is changing and what these changes may mean for each of the career anchors. Developmental activities that participants can use as next steps in their career development The fifth edition of Career Anchors will help you analyze, assess, and understand your particular career anchor to help you chart the future of your career development"--